Kinematics of cross-country sit skiing during a Paralympic race - Bernardi, M.; Janssen, T.; Bortolan, L.; Pellegrini, B.; Fischer, G.; Schena, F. (Journal of Electromyography and Kinesiology, 2013)
The study had three purposes: to verify a hypothesized speed decrease during the 15km cross-country sit skiing (CCSS) race; documenting this possible fatigue effect (speed decrease), to evaluate changes among the four laps in kinematics parameters (cycle speed, cycle duration, cycle length, duty cycle (percentage ratio between pushing and total cycle duration), pole inclination, trunk inclination and shoulder-hand distance); to compare the kinematics parameters in cross-country sit skiers of different level. Video recordings were carried out during the 2006 Turin Winter Paralympic Games with two conventional digital video-cameras positioned on a flat and an uphill (8.3°) track, respectively. Better performing skiers (G1) had significantly higher speeds than worse performers (G2) both in the flat (6.54±0.13 vs. 5.89±0.50ms-1 and 5.55±0.14 vs. 4.62±0.22ms-1 in the first and last lap, respectively) and in the uphill track (3.67±0.45 vs. 3.05±0.59ms-1 and 3.20±0.36 vs. 2.26±0.36ms-1 in the first and last lap, respectively). The G1 athletes were able to maintain the high-speed better than the G2 over the entire race. Significant differences in cycle length and duty cycle between groups would be justified by the higher physical fitness of G1 skiers.